2012
DOI: 10.1002/app.35667
|View full text |Cite
|
Sign up to set email alerts
|

The effects of technological compatibility for silicone rubber/fluororubber blends

Abstract: In this study, silicone rubber (SR) and fluororubber (FKM) blends were prepared and their properties were investigated. The crosslinking rate in the blends was increased with increase of SR content due to the silica filler existing into SR. As the content of FKM in the blends increases, the thermal decomposition temperature of the blends tended to increase and the thermal stability of 25/75 SR/FKM blend was higher than that of any other blends ratios. With the increase of FKM content in the blends, the contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…The contact angle test was applied to characterize the polarity of samples, which could reflect its wettability and display a substantial correlation with the adhesion property in some bonding systems. [29][30][31] The surface energy of the PPS surface was calculated using Neumann equation 32 : In Neumann's approach, g LV is the surface tension of the liquid in equilibrium with its own vapor, represents the contact angle, g s is the surface tension of the solid in equilibrium with the saturated liquid vapor, which can be regarded as the surface energy, and is an empirical constant that depends on the system under investigation but is typically set to be equal to 0.0001247 (mJ m À2 ) À2 . 32 Figures 6 and 7 demonstrate the contact angle and surface energy of PPS surface after air DBD plasma treatments with different parameters.…”
Section: Influence Of Air Plasma Treatment On Pps Surface Propertiesmentioning
confidence: 99%
“…The contact angle test was applied to characterize the polarity of samples, which could reflect its wettability and display a substantial correlation with the adhesion property in some bonding systems. [29][30][31] The surface energy of the PPS surface was calculated using Neumann equation 32 : In Neumann's approach, g LV is the surface tension of the liquid in equilibrium with its own vapor, represents the contact angle, g s is the surface tension of the solid in equilibrium with the saturated liquid vapor, which can be regarded as the surface energy, and is an empirical constant that depends on the system under investigation but is typically set to be equal to 0.0001247 (mJ m À2 ) À2 . 32 Figures 6 and 7 demonstrate the contact angle and surface energy of PPS surface after air DBD plasma treatments with different parameters.…”
Section: Influence Of Air Plasma Treatment On Pps Surface Propertiesmentioning
confidence: 99%
“…Accordingly, some attempts have been made to prepare FKM/SR blends, combining the excellent oil resistances properties of FKM and low temperature resistances of SR. By mechanical blending, the FKM/SR blends are expected to partially substitute expensive fluorosilicone rubber to some extent [15][16][17] . However, after vulcanization, the cured FKM/SR blends are thermosetting material.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that 75 wt% of FKM and 25 wt% of MVQ combines superior compatibility. [ 26 ] The effect of FKM‐g‐vinyltriethoxysilane in the FKM/MVQ rubber blend as an effective compatibilizer has also been studied and the results showed that 9 phr loading of the compatibilizer enhances the mechanical, thermal properties and improves filler to rubber interactions. [ 27 ] Wang et al have studied the dynamically cured polyvinylidene fluoride (PVDF)/MVQ/FKM blend system with the partial replacement of MVQ with FKM.…”
Section: Introductionmentioning
confidence: 99%